Combined flexor sheath and gastrocnemius aponeurosis flap for the treatment of chronic calcified Achilles tendon rupture: a case report - Tu, Shuangqiang; Li, Zhongshan; Xiao, Mengying; Zhu, Wensheng; Shao, Yi (Frontiers in Surgery, 2025)
IntroductionThe Achilles tendon is the largest tendon in the human body and is prone to rupture when subjected to excessive dorsiflexion trauma of the ankle joint. The primary goal of treatment is to restore limb function; however, there remains considerable debate regarding the optimal management strategy.Patient concernsWe report a patient presenting with chronic Achilles tendon rupture accompanied by calcification of the tendon, which caused persistent pain and functional limitation of the affected limb.DiagnosisChronic Achilles tendon rupture with associated tendon calcification, with a tendon defect measuring approximately 6 cm on preoperative imaging, confirmed by clinical examination and imaging evaluation.InterventionsThe patient underwent surgical removal of the calcified lesion, followed by reconstruction of the tendon defect using a gastrocnemius aponeurosis flap combined with the Achilles tendon sheath.OutcomesPostoperative recovery was favorable, and at the 6-month follow-up, the patient achieved satisfactory ankle function with an AOFAS score of 89, a VISA-A score of 91, and an ATRS score of 90. At the 12-month follow-up, functional outcomes remained stable, with an AOFAS score of 95, a VISA-A score of 96, and an ATRS score of 94, confirming sustained recovery and tendon integrity.ConclusionThis case highlights a feasible surgical strategy for chronic Achilles tendon rupture with calcification, which may provide an alternative approach for tendon reconstruction in patients with sheath proliferation and calcified lesions.